Neurodevelopmental difficulties in children with idiopathic clubfoot - Lööf, E.; Andriesse, H.; Broström, E.; André, M.; Bolte, Sven (Wiley-Blackwell Publishing Ltd., 2019)
© 2018 Mac Keith Press Aim: To evaluate neurodevelopmental difficulties in children with idiopathic clubfoot. Method: A cross-sectional study of 106 children (29 females, 77 males; aged 8–10y) with idiopathic clubfoot and 109 age-, sex-, and residential area-parallelized children from the general population. Neurodevelopmental difficulties were assessed using the parent-report Five to Fifteen (FTF) questionnaire. Group differences were analysed for FTF domains, subdomains, and items. The 90th centile cut-off of the general population on FTF and the parent-based disease-specific instrument (DSI) were used to evaluate clinical relevance of neurodevelopmental symptoms in idiopathic clubfoot. Results: Modest group differences were found for several FTF domains (motor skills, perception, and language) and subdomains (gross and fine motor skills, relation in space, comprehensive and expressive language skills). Thirty-one per cent of the children with idiopathic clubfoot scored in the clinically significant range on 2 or more FTF domains. DSI scores were lower in this subgroup. Interpretation: Findings indicate a moderate and selective increase of neurodevelopmental difficulties in children with idiopathic clubfoot as a whole, especially in the areas of motor skills, perception, and language. Idiopathic clubfoot with marked neurodevelopmental symptoms are associated with less satisfaction of the clubfoot treatment. Our results recommend awareness of neurodevelopmental difficulties in the assessment and treatment of idiopathic clubfoot. What this paper adds: A substantial minority of children with idiopathic clubfoot show neurodevelopmental difficulties. Children with idiopathic clubfoot might present additional difficulties in motor skills, perception, and language. Children with idiopathic clubfoot and marked neurodevelopmental symptoms show poorer parent-reported clubfoot treatment satisfaction. Neurodevelopmental difficulties should be considered in clinical practice of idiopathic clubfoot.